Uzależnienia jako przejaw dewiacji społecznej - Kuraciński, Edward (Seminare. Poszukiwania naukowe, 2007)
This article represents considerations for social deviation, specifically various modifications of addictions. First of all, author analyzes opinions such sociologists as Durkheim or Merton. The social deviation may be defined as the unenforcement of rules and recognized patterns of behavior. The root causes of addictions are psychological factors as compulsive behaviors and emotional disorders, social factors as abnormal socialization, social structures for example nonfunctional families and subculture of friendly groups, cultural as lack of confidence and public consent to different deviations and political as injustice , social inequalities, nepotism, corruption and economical and political transformation. It is significant that the other reasons of subjection between other things are such social problems as unemployment or poverty. Put another way, the problem of addictions is not really a sociological one but psychological, political, cultural, economical so that we can not to treat with disregard it and must elaborate eligible prophylaxis preventing pathologies.